Physiological activities of cocoa trees induced by soil and foliar applications of boron fertilizer - Dewi HS, Endang Sri; Yudono, Prapto; Susilaputra, Eka Tarwaca; Purwanto, Benito Heru (Universitas Sebelas Maret, 2023)
This study investigates the impact of boron fertilizer on physiological activities of cocoa trees, specifically focusing on boron content, nitrogen content, nitrate reductase activity, chlorophyll content, and photosynthesis rate in cocoa plant leaves. This research was arranged in a randomized complete block design with two treatment factors, which were the type of boron fertilizer application (soil and foliar fertilizer), and the dose of boron fertilizer (1.5, 3, 4.5, and 6 g plant−1 with 0 g plant−1 as a control). Data were then analyzed for variance differences (ANOVA) with α = 5%, followed by the Tukey test, and contrast orthogonal for comparing treated and control plants. The results showed that the dose of boron fertilizer and the type of fertilizer application used have a significant effect on the physiological activity of the cocoa plant. The dose of boron with soil application affects physiological activity in a linear pattern where each additional dose of boron will increase the activity of nitrate reductase, chlorophyll content, and photosynthetic rate. The dose of boron with foliar application affects physiological activity in a quadratic pattern, where the dose of boron in the range of 3 g plant−1 is the optimum dose that gives maximum results on nitrate reductase activity, chlorophyll content, and photosynthetic rate in the cocoa leaves. Therefore, it is considered that the application of boron fertilizer at a dose of 3 g plants−1 with the foliar application is more efficient in increasing physiological activity compared to the dose of boron with soil application.